(untitled) (Research, Society and Development, 2022)
Viruses have complex evolutionary relationships, and several strategies have been used in an attempt to classify the phages that infect S. thermophilus. In this study, we used a wide range of complementary methods, including comparative genomics, core genome analysis, and signature genes phylogenetics, to show that the S. thermophilus phages are organized into 142 species and five genera (three of them new) and that due to their genetic diversity, the classification at family level varies according to the classification criteria used. No significantly conserved genes were identified among the 183 genomes evaluated. However, the genes encoding holin protein were conserved in more than 95% of genomes. The holins analysis suggests that at least two α-helix are required for protein function within S. thermophilus phages. This study expanded the of knowledge about the genetic diversity and evolution of streptococcal phages, both fundamental to promoting control strategies and minimizing failures in milk fermentation processes.